 Important for :
1
What is the LCM of a3b – ab3,  a3b2 + a2b3 and ab(a + b)?
» Explain it
A
Let f(x) = a3b – ab3 = ab(a2 – b2) = ab(a – b)(a + b)

g(x) = a3b2 + a2b3 = a2b2(a + b)

and h(x) = ab(a + b) = ab(a + b)

∴   LCM of  [f(x), g(x), h(x)]  =  a2b2(a + b)(a – b)  =  a2b2 (a2 – b2)

Hence, option A is correct.

2
What is the HCF of the polynomials x4 – 3x + 2, x3 – 3x2 + 3x – 1 and x4 – 1?
» Explain it
A
Let f(x)  =  x4 – 3x + 2 = (x – 1) (x3 + x2 + x – 2)

g(x)  =  x3 – 3x2 + 3x – 1 = (x – 1)3

and h(x)  =  x4 – 1 = (x – 1) (x + 1) (x2 + 1)

∴    HCF of  [f(x), g(x), h(x)]  =  (x – 1)

Hence, option A is correct.

3
If (x – 6) is the HCF of x2 – 2x – 24 and x2 – kx – 6, then what is the value of k?
» Explain it
B
Given that, (x – 6) is the HCF of x2 – 2x – 24 and x2 – kx – 6, i.e., (x – 6) is a factor of both expression,

Let  f(x)  =  x2 – 2x – 24  and  g(x)  =  x2 – kx – 6

Now,  f(x) = g(x) at (x = 6)

⇒    (6)2 – 2(6) – 24 = (6)2 – k(6) – 6 ⇒    36 – 12 – 24 = 36 – 6k – 6

⇒    0 = 30 – 6k   ⇒  6k = 30   ⇒  k = 5.

Hence, option B is correct.

4
The HCF of (x4 – y4) and (x6 – y6) is
» Explain it
A
Let  f(x) = (x4 – y4)  =  [(x2)2 – (y2)2]

= (x2 – y2) (x2 + y2)

= (x – y)(x + y)(x2 + y2)

g(x) = (x6 – y6) = (x3)2 – (y3)2

= (x3 + y3) (x3 – y3)

= (x + y) (x2 – xy + y2)(x – y) (x2 + xy + y2)

= (x – y)(x + y)(x2 – xy + y2)(x2 + xy + y2)

∴   HCF of  [f(x), g(x)]  =  (x – y)(x + y)  =  x2 – y2

Hence, option A is correct.

5
What is the LCM of x2 + 2x – 8, x3 – 4x2 + 4x and x2 + 4x?
» Explain it
A
f(x) = x2 + 2x – 8 = x2 + 4x – 2x – 8

= x(x + 4) – 2(x + 4) = (x – 2)(x + 4)

g(x) = x3 – 4x2 + 4x = x3 – 2x2 – 2x2 + 4x

= x2(x – 2) – 2x(x – 2) = (x2 – 2x)(x – 2)

= x (x – 2) (x – 2)

h(x) = x2 + 4x = x(x + 4)

So, LCM of  [f(x), g(x), h(x)]  =  x(x – 2)(x + 4)(x – 2)  =  x(x + 4)(x – 2)2

Hence, option A is correct.